Biblioteca scriitorilor: cazul Bibliotecii Municipale „B.P. Hasdeu”: Maria Pilchin - admin, admin (BIBLIOPOLIS, 2023)
The term of library and librarian has recently become so resilient that it encompasses a multitude of specializations in human activity. We come up with an applied approach to the literary field in our space, with a synthesis focused on the cultural policies of the library in the field of writing. From beginners to established writers, from the writer hired and integrated into the library network team to the guest writer in the programs – all of these aspects make for an effective collaboration with the writing guild. The investigation of the writer’s importance in the library of a city, of the impact of his work and activity on the library user – this is the purpose of this study.